Perceptions of Iowa Beginning Farmers Toward the Delivery of Education - Larry D. Trede; Scott Whitaker (Journal of Applied Communications, 1998)
The results of this research show that Iowa beginning farmers prefer radio and information services for the delivery of beginning farmer education. At the same time, these same farmers viewed the Extension Service as an important educational provider. Research was conducted to identify the perceptions of beginning farmers toward education, educational providers, and educational media. A sample of beginning farmers was surveyed in 1997. This study revealed they prefer on-site educational instruction, single meetings, community-based education, and were “neutral” (had no opinion) about the future usefulness of cutting-edge technologies as a delivery method. The results of this study should be useful to educational providers who plan and deliver education to beginning farmers.